UI/UX Design of GoHealth Mobile Application Using Design Thinking Approach - Al Fata, Umar; Mauladi, Teguh Ade; Fikri, Muhamad; Huda, Miftahul (Journal Mobile Technologies (JMS), 2026)
The swift pace of digital change in healthcare has opened new doors for mobile health services (m-health), but users in developing areas still face major hurdles, like high consultation costs, no real-time updates on health facility activities, and poor usability of current platforms. This study wants to create a user-focused mobile health app, "GoHealth," using the Design Thinking approach to solve these exact problems. The research framework combines the five steps of Design Thinking—Empathize, Define, Ideate, Prototype, and Test—with a specific focus on improving user interaction and accessibility. Quantitative results showed an overall Task Success Rate (TSR) of 92%, though specific tasks like 'Input Form' and 'Payment' initially had a lower success rate of 80% before iteration. The high-fidelity prototype has a simplified consultation flow, real-time location tracking for health facilities, and a curated health literacy module. Usability testing with representative users (n=5) using the Unmoderated Usability Study method showed a high task completion rate but identified areas for improvement in micro-interactions. This study concludes that a human-centered approach significantly enhances perceived utility and efficiency in mobile health applications by bridging the gap between technological capability and user needs.